Aesthetics of the Bidayuh Community Kasah Mat Annah Rais Longhouse - Shaik Azahar, Shaik Hussain; Athirah Shahira’a, Abdullah (Secholian Publication, 2022)
Kasah mat or Kelasah mat is one of the handicrafts known in the Bidayuh ethnic group. Weaving the Kasah mat is a heritage art made of rattan and woven using wood bark. This study is about the aesthetics of Kelasah mat of the Bidayuh community located in Annah Rais Longhouse. Annah Rais Longhouse is a village located in the foothills of the Borneo Highlands and must -visit tourism which are located near Kuching; Sarawak Therefore, the focus of this study is the material of mat production. This study was conducted with qualitative method and interviewed the residents of this longhouse also known as the producer of this Kasah mat. The study revealed that besides concentrating on reviving the culture value, the community of Bidayuh can generated their income through selling this culture product. As a conclusion, the materials used by the manufacturer is to highlight the aesthetics of a mat that is the pride of the Bidayuh people.